PENINGKATAN EFEKTIVITAS PEMBELAJARAN MELALUI PENGUATAN SUPERVISI AKADEMIK DAN DISIPLIN KERJA - Reni Herawati; Rita Retnowati; Sutji Harijanto (JURNAL MANAJEMEN PENDIDIKAN, 2021)
LEARNING EFFECTIVENESS IMPROVEMENT THROUGH ACADEMIC SUPERVISION AND WORK DISCIPLINE STRENGTHENINGThe purpose of this study was to empirically determine  the enhance of teaching effectiveness. Research respondents were permanent teachers of private high schools in Bogor City. The number of samples were 131 teachers who were established by using proportional random sampling technique. The method used was the correlational method. Hypothesis testing was carried out by using parametric statistical analysis in the form of linear regression analysis, correlation analysis, and partial analysis where a significance level of α = 0.01 and α = 0.05. The research came up with three conclusions. Firstly, there was a very significant positive relationship between academic supervision and the teaching effectiveness where the correlation coefficient of ry1 = 0.824. Secondly, there was a very significant positive relationship between work discipline and the teaching effectiveness, where the correlation coefficient of ry2 = 0.66. Thirdly, there was a very significant positive relationship between academic supervision and work discipline together with the teaching effectiveness, where the correlation coefficient of ry.12 = 0.84. Based on the results of the research, it can be concluded that the teaching effectiveness can be enhanced by strengthening academic supervision and work discipline. Results of the SITOREM analysis indicated that several priority indicators need to be improved, such as; assessment of work results, problems solving assistance, self-control during working, teachers’ willingness to carry out obligations, sucessfullness in conducting learning activity, and successfulness in managing learning activity. Based on the results above, it can be concluded that the teaching effectiveness can be enhanced by strengthening academic supervision and work discipline.